2016
DOI: 10.3390/nu8090530
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutrition in Periodontal Health: An Update

Abstract: Periodontal health is influenced by a number of factors such as oral hygiene, genetic and epigenetic factors, systemic health, and nutrition. Many studies have observed that a balanced diet has an essential role in maintaining periodontal health. Additionally, the influences of nutritional supplements and dietary components have been known to affect healing after periodontal surgery. Studies have attempted to find a correlation between tooth loss, periodontal health, and nutrition. Moreover, bone formation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
161
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(174 citation statements)
references
References 148 publications
3
161
0
10
Order By: Relevance
“…The role of nutrients and vitamins for periodontal health and wound healing has been extensively investigated in other studies. 22,23 The wound healing process is typically composed of three consecutive and overlapping stages, including inflammation, new tissue formation, and remodeling. 24 In addition, the healing process involves a cascade of events, such as blood clot formation, neutrophil adhesion, and formation of granulation tissue, which is followed by connective tissue reepithelialization and the formation of mature tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of nutrients and vitamins for periodontal health and wound healing has been extensively investigated in other studies. 22,23 The wound healing process is typically composed of three consecutive and overlapping stages, including inflammation, new tissue formation, and remodeling. 24 In addition, the healing process involves a cascade of events, such as blood clot formation, neutrophil adhesion, and formation of granulation tissue, which is followed by connective tissue reepithelialization and the formation of mature tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The role of nutrients and vitamins for periodontal health and wound healing has been extensively investigated in other studies 22,23. The primary outcome of this clinical trial was that postoperative administration of vitamin C improved the healing potential in patients suffering from chronic periodontitis and patients treated with GBR or Bio-Oss Collagen grafts.…”
mentioning
confidence: 99%
“…Poor nutrition has also been found to be a major factor in the development of periodontal diease . While the exact mechanism by which poor nutrition leads to periodontal disease has not been fully elucidated, nutritional factors modulate the inflammatory response and deficiencies result in an exaggerated response .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the nutrients and food consumed have also been reported to be correlated with periodontal disease. Shariq Najeeb et al suggested that decreased consumption of vitamins and minerals, particularly vitamin C, which has antioxidant activity, was highly associated with periodontal disease; however, vitamin C supplementation was not effective in treating periodontal disease [15]. Varun Kulkami et al showed a similar intake of particular nutrients in patients with and without periodontal disease.…”
Section: Introductionmentioning
confidence: 99%